A Pengaruh Presiden dalam Putusan Mahkamah Konstitusi Perkara nomor 90/PUU-XXI/2023 terkait usia minimal calon presiden dan calon wakil presiden: Hukum Tata Negara - darma, ista; Kuswan Hadji; Muhammad Fardan Valenko; Nicholas Adi Kusuma; Sheva Andika Ramajagandhi; Basuki Basuki (Jurnal Hukum dan Sosial Politik, 2024)
This research tries to analyze the influence of President Jokowi in the decision of Case number 90/PUU-XXI/2023 regarding the minimum age of presidential candidates and vice presidential candidates. We know that President Jokowi's name has recently become a topic of conversation, with rumors that he wants to nominate his son. became vice president, but in this case President Jokowi experienced a constitutional obstacle, namely that his son, Gibran, was still 36 years old. Who cannot be nominated because the requirement to become vice president in the 2024 presidential election must be 40 years old. This is an obstacle for President Jokowi to nominate his son to be vice president, who according to rumors has emerged as a pair with Prabowo Subianto. This research tries to understand how much influence there is in political intervention on the State Administration system and the influence of the family in the Constitutional Court's decision Number 90/PUU-XXI/2023. The results of the research show that the Constitutional Court's decision regarding the age limit for presidential and vice presidential candidates in October 2023 is a judicial decision that shows the family's interests because first, the discussion of the judicial review of the law is procedurally flawed